Experiences with adolescent health service provision and perceived barriers of adolescent friendly health services in Ibadan, Nigeria: Health care providers’ perspective (2020)
Health care workers play key roles in the provision of adolescent friendly health services but there have been reports of difficulties experienced by health care workers when providing health services to adolescents. Understanding the reasons for these difficulties is important to ensure the continuous provision of adolescent friendly health services. This study therefore explored the experiences of health care workers in Ibadan with adolescent health service provision and the barriers they encounter while providing this service. This was an exploratory cross-sectional study where key informant interviews were conducted using interview guide with 11 health care workers. Data was analysed using thematic analysis method. There were seven nurses and four doctors, nine females and two males. Many of the health workers had little or no training in adolescent health and some were confident that they could manage adolescents well even though they had no specialised training in adolescent health. Good training, patience and good communication skills were mentioned as important skills for providing adolescent health services. The common barriers they encountered while caring for adolescents include lack of skills, poor clinic settings, lack of protocol for correct handling of adolescents and non-cooperation of adolescents. These health workers had a fair knowledge of how adolescent friendly services and clinics should be but most lack the required skills to provide these services. The clinic settings were also not adolescent friendly. Specialized training in adolescent health and implementation of existing adolescent health policies are required to ensure adolescent friendly services for adolescents in Ibadan.